Study of Multiple Crack Interaction on the Surface of Solid Shaft Using Ansys Finite Element Analysis - Mohd Yusoff, Seri Melati Izzati; Ismail, Al Emran (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study uses ANSYS Workbench software to examine the interaction of single and multiple cracks on the surface of a solid shaft under different stress circumstances using the finite element method (FEM). Investigating the effects of various fracture depth ratios, aspect ratios, and placements on the stress intensity factors (SIFs) is the goal of the study. The study guarantees that the results are generally applicable by normalizing the SIF values according to the loadings, which include internal pressure, bending moment, tension force, and torsion moment. Validating the data is part of the approach to ensure that the simulation process is accurate. By anticipating probable failure areas and enhancing design tactics to avoid catastrophic failures in mechanical systems, the findings help in the understanding of the structural integrity of shafts with many fractures.